Semantic and cultural equivalence of the working alliance inventory short-revised scale for therapeutic alliance in family medicine - Petek, Davorina (Zdravstveno varstvo, 2019)
Introduction: Therapeutic alliance is a term most commonly associated with psychotherapeutic treatment, but recently its use has become increasingly significant in the other fields of medicine. An increasing amount of evidence implies that the quality of the therapeutic alliance between the doctor and patient substantially affects treatment outcomes. A European consensus chose the Working Alliance Inventory - Short Revised (WAI-SR) scale as the most efficient for European primary care. This paper presents the process of establishing the semantic and cultural equivalence of the two WAI-SR scales in Slovene. Method: As a part of a larger international project, a group of four experts translated the two WAI SR scales (physician and patient versions) from English into Slovene. Twenty-six Slovenian family medicine doctors participated in the process of obtaining semantic, idiomatic, experiential and conceptual equivalence in translation using a Delphi consensus procedure. Afterward, a cultural equivalence was made to adapt the translations within the national context. Results: Agreement on translation was achieved after two Delphi rounds. The back-translation and cultural equivalence were accomplished without major problems, with some minor additional linguistic corrections. Conclusion: A Slovene version of the WAI-SR scale was successfully adapted and is available for further scale validation and research on therapeutic alliance.
Keywords: Delphi consensus procedure; Delphi metode; družinska medicina; family medicine; terapevtsko zavezništvo; therapeutic alliance